Laure Ghorayeb: Black on White - Saradar Collection (Beirut Kaph Books, 2019)
This publication looks back on her transition from writer to painter. "Laure Ghorayeb: Black on White" is the second publication in the Saradar Collection x Kaph Books series and includes texts by Venetia Porter and Dr. Maha Azizé Sultan as well as a conversation between the artist and her son Mazen Kerbaj. Editors: Mazen Kerbaj, Sandra Dagher & Lina Kiryakos, Nour Salame; Saradar Collections x Kaph books.
English
Keywords: N5198-5299 Visual Arts- Private collections and collectors